2008
DOI: 10.1002/fld.1845
|View full text |Cite
|
Sign up to set email alerts
|

Galerkin technique based on beam functions in application to the parametric instability of thermal convection in a vertical slot

Abstract: SUMMARYA Fourier-Galerkin spectral technique for solving coupled higher-order initial-boundary value problems is developed. Conjugated systems arising in thermoconvection that involve both equations of fourth and second spatial orders are considered. The set of so-called beam functions is used as basis together with the harmonic functions. The necessary formulas for expressing each basis system into series with respect to the other are derived.The convergence rate of the spectral solution series is thoroughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Following [11,13], we consider natural convection in a vertical fluid with differentially heated lateral surfaces. The x-axis is across the slot and y is taken as the vertical coordinate.…”
Section: Convection In a Vertical Slotmentioning
confidence: 99%
See 4 more Smart Citations
“…Following [11,13], we consider natural convection in a vertical fluid with differentially heated lateral surfaces. The x-axis is across the slot and y is taken as the vertical coordinate.…”
Section: Convection In a Vertical Slotmentioning
confidence: 99%
“…which are termed the Cattaneo, Rayleigh, and Prandtl numbers, respectively. It can be shown that in terms of the stream function (see [11,13] and the literature cited therein), the ID equation of motion reads…”
Section: Convection In a Vertical Slotmentioning
confidence: 99%
See 3 more Smart Citations